INFORMATION AND COMMUNICATION TECHNOLOGIES SUITABLE FOR THE EDUCATION OF PUPILS WITH SPECIAL EDUCATIONAL NEEDS - MEIER, Miroslav (Trends in education, 2014)
The paper presents part of the results of the project Education of pupils with special educational needs, and information and communication technologies, which was devoted to the issue of the use of information and communication technologies in the education of pupils with special educational needs at elementary school.
Keywords: education; information and communication technologies; special educational needs; teachers; pupils.